Sedation for gastroscopy: Is it an adequately understood and informed choice?. (November 2016) - Quinn, L.; Kelly, M.; Khan, A.; Irwin, R.; Khan, W.; Barry, K.; Waldron, R.; Khan, I.
Abstract Introduction Sedation uptake rates for oesophagogastroduodenoscopy (OGD) vary greatly. Issues concerning adequate information and consent have been raised. Additionally, patient comprehension of sedation options is inconsistent. Methods A closed ended questionnaire was created and delivered to assess patient understanding regarding sedation prior to OGD. The questionnaire was based on British Society of Gastroenterology guidelines. Results One hundred and eleven patients were recruited. 90 % of the sedated and 73 % of the unsedated patients were satisfied with their respective decisions (OR 0.283, *p = 0.01). 65 % were unaware of basic differences between conscious sedation and general anesthesia, and 37 % were unaware that driving is permitted after having throat spray alone. The most informed of the age groups had the lowest uptake of sedation and the least informed had the highest uptake. Conclusion The decision to undergo gastroscopy with or without sedation is not a sufficiently informed one. This study highlights the need for the widespread dissemination of good quality information to inform patients better regarding sedation prior to OGD.